Perbandingan Suhu, Kelembapan, dan Bobot Badan Ayam Broiler pada Kandang Closed House dengan dan tanpa Naungan : Comparison of Temperature, Humidity, and Broiler Chicken Body Weight in Closed House Systems with and wihout Tree Shade - Fikri, Muhammad Rijalul; Tugiyanti, Elly; Widiyanti, Rahayu (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2026)
Background: Broiler chickens are fast-growing poultry that require optimal housing environmental conditions to support growth performance and production efficiency. Closed house systems are designed to control temperature, humidity, and ventilation. However, external environmental factors, such as the presence of tree shade, may influence the internal microclimate of the house, particularly by reducing heat exposure from direct solar radiation. Purpose: This study aimed to compare the microclimate conditions (temperature and humidity) and body weight of broiler chickens reared in closed house systems with and without tree shade. Methods:The study was conducted for 35 days in two closed house facilities, each housing 9,000 broiler chickens. Temperature and humidity were recorded daily, while body weight was measured at 35 days of age by randomly sampling 30 chickens from each house. Temperature and humidity data were analyzed using the Mann–Whitney test, whereas body weight data were analyzed using the Independent Sample T-test at a 5% significance level. Results: The average temperature and humidity in the shaded house tended to be lower than those in the unshaded house, although no statistically significant differences were observed. In contrast, broiler chickens reared in the shaded house exhibited higher body weight compared to those in the unshaded house. Conclusion: The presence of tree shade in closed house systems contributes to creating more favorable microclimate conditions and supports increased body weight in broiler chickens.